The Implementation of Cooperative Learning in Teaching Reading Comprehension to Introvert and Extrovert Students - Annas Alkhowarizmi; Fiki Setiawan; Nina Herlina (English Language Education Department, Universitas Majalengka, 2024)
Traditional teacher-centered approaches are being replaced by collaborative learning methods like cooperative learning. This research explores the benefits of cooperative learning for both introverted and extroverted students. A pre-experimental, one-group pretest-posttest design was employed. The participants were first-semester students at a health science institute (n=18). Purposive sampling was used to select a group of students. The researcher administered a personality assessment to classify students as introverts or extroverts. The findings showed that cooperative learning improved reading comprehension for both extroverted and introverted students. Extroverts benefited from the interactive and collaborative aspects of cooperative learning. Introverts, on the other hand, thrived in an environment that allowed for thoughtful participation and reflection. The results also suggest that personality traits moderate the effects of cooperative learning on reading comprehension. This study highlights the effectiveness of cooperative learning in enhancing reading comprehension for students with diverse personalities. It emphasizes the need for educators to consider individual characteristics when designing instructional strategies. By incorporating cooperative learning and acknowledging the influence of personality traits, educators can create more personalized and effective teaching practices that cater to the diverse needs of students in language classrooms.